Ferroelectric materials with photoluminescent properties - Bouquet, V; Vasconcelos, NSLS; Aguiar, R.; Pinheiro, C. D.; Leite, E. R.; Pizzani, P. S.; Varela, P. A.; Longo, Elson [UNESP]; Boschi, T. M.; Lanciotti, F.; Machado, MAC (Taylor & Francis Ltd, 2003)
Amorphous LiNbO3 thin films processed by polymeric precursor method exhibited efficient luminescence at room temperature. The films were deposited on silicon substrates and treated at 200degreesC for different times. The photoluminescence emission yield decreases with the increase of the treatment time and disappears for crystalline films. A theoretical-experimental study was performed on amorphous and crystalline materials to understand the influence of the defects on the photoluminescence properties. The theoretical band gap obtained by the difference of energy between the HOMO and LUMO levels is larger for crystalline structure when compared with amorphous material. This result, which is in agreement with experimental band gaps obtained from optical measurements, revealed the emergence of new electronic levels for the amorphous material, which are localized in the wide band gap of the crystalline structure. These new electronic levels may explain the photoluminescence observed at room temperature for LiNbO3 amorphous films.
Keywords: LiNbO3; amorphous thin films; photoluminescence; Pechini